Odporne metody w konstrukcji portfela wieloskładnikowego - Kaszuba, Bartosz (Robust Statistical Methods for Portfolio Construction, 2009)
The article presents a comparison of minimum variance portfolios, determined using the maximum likelihood estimators of the covariance matrix, with portfolios determined using robust estimators of the covariance matrix. The aim of the dissertation is to compare the risks of the discussed portfolios, and to designate the minimum variance portfolios by applying select robust estimators of the covariance matrix. All the created portfolios are portfolios which change with time. The research is based on real data, coming from the Warsaw Stock Exchange. The article demonstrates usefulness of methods which apply shrinkage estimators. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 165-172